2021
DOI: 10.2478/hukin-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biological Maturity on the Muscular Strength of Young Male and Female Swimmers

Abstract: The present study compared the evolution of strength and muscle mass in swimmers of both sexes across different chronological and biological ages. Seventy-six swimmers (55 males and 21 females) from 10 to 20 years of age underwent evaluations of sexual maturation using the developmental stage of the genitals (G1, G2, G3 G4 and G5) and pubic hair (P1, P2, P3, P4 and P5) (Tanner criteria), lean mass using the dual-energy X-ray absorptiometry method, and isokinetic strength of the knee extensor muscles. Boys did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
3
9
0
3
Order By: Relevance
“…Estudos com maior tamanho amostral estão em andamento. 2 A influencia de outros fatores potencialmente modificadores do torque isométrico, tais como fatores socioeconômicos e nível de atividade não foram controlados.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos com maior tamanho amostral estão em andamento. 2 A influencia de outros fatores potencialmente modificadores do torque isométrico, tais como fatores socioeconômicos e nível de atividade não foram controlados.…”
Section: Discussionunclassified
“…Assim, é importante para entender o desempenho muscular ao longo do desenvolvimento biológico do indivíduo. 2 Dentro da avaliação do desempenho muscular, o torque muscular isométrico é uma variável que pode ser obtido por dinamômetros portáteis quando se considera o comprimento do segmento corporal multiplicando-o pela força. 3 Entretanto, o padrão ouro para avaliar torque é o dinamômetro isocinético 4 que fornece dados numéricos e gráficos.…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…Another factor that could affect strength balance among adolescent athletes is the pubertal phase. From puberty, a marked gain in muscle strength is evident [24,25]. However, it is unknown whether the abrupt muscular strengthening that occurs during puberty is a balanced gain in all the muscles of the lower limbs or whether the specific and repetitive muscular demand (numerous turns during swimming training) added to the abrupt strength gain characteristic of puberty can generate an imbalance between knee flexor and extensor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…31 More recently, a study of 40 prepubertal and 40 postpubertal children and adolescents found that knee extensor and flexor strength is higher in boys, but only at the postpubertal stage, 29 a finding that was confirmed by a study on swimmers that assessed only knee extensor strength. 4 All 4 studies were based on cross-sectional data collected at 1 time point rather than longitudinal changes in muscle strength in young athletes over time. In terms of longitudinal studies, 1 study included male participants only, 10 while another study 16 on 8- to 15-year-old participants compared boys and girls of similar biological age instead of considering maturation, and found that the knee flexors and extensors of boys were stronger at ages 14 and 15 years only.…”
mentioning
confidence: 99%